Mastercases : shoulder and elbow surgery - Field, Larry D.; Savoie, Felix H., III (MasterCases., 2003)
Surgical techniques for shoulder and elbow management are presented in a case-based format and illustrated with color and b & w intraoperative photos and radiographs. Some conditions covered include rotator cuff disorders, fractures, tendonitis, and neuropathies. The book will be useful to orthopedic surgeons, sports medicine specialists, and residents. The authors are affiliated with the Department of Orthopedic Surgery at the University of Mississippi.